HDR interventional radiotherapy (brachytherapy) in the treatment of primary and recurrent head and neck malignancies. Issue 6 (30th January 2019) - Bussu, Francesco; Tagliaferri, Luca; Mattiucci, Giancarlo; Parrilla, Claudio; Rizzo, Davide; Gambacorta, Maria Antonietta; Lancellotta, Valentina; Autorino, Rosa; Fonnesu, Carla; Kihlgren, Caterina; Galli, Jacopo; Paludetti, Gaetano; et al.
Abstract: Background: Interventional radiotherapy (brachytherapy; IRT) reemerged in the last decades as a potentially useful tool in head and neck oncology after a set of clear technical improvements were developed. Methods: Sixty‐one high dose ratio (HDR) IRT treatments were recommended and performed on 58 patients. We classified the cases into four relatively homogeneous groups based on the clinical needs that led to the recommended IRT. Also, we separately evaluated primary and recurrent cases. Results: Disease‐specific survival was significantly different among the four treatment groups. The group with the best prognosis was the cohort treated locally by exclusive interstitial IRT for resectable midface malignancies (2‐year relapse‐free survival = 82%, disease‐specific survival = 89%). Conclusion: HDR IRT is a valuable tool in well‐defined clinical situations and, in particular, in recurrences. In midface malignancies, it could become the preferred primary treatment.